Cancer : principles & practice of oncology. Primer of the molecular biology of cancer - DeVita, Vincent T., Jr., 1935-; Lawrence, Theodore S.; Rosenberg, Steven A. (Philadelphia : Wolters Kluwer, 2015)
Understand and apply the scientific advances that are revolutionizing cancer research and practice! Derived from DeVita, Hellman, and Rosenberg's Cancer: Principles and Practice of Oncology - widely hailed as the definitive clinical reference in oncology - the second editon of this popular Primer focuses on the molecular biology information that is of critical importance to research scientists and clinical oncologists alike. Get up-to-date, dependable coverage of every important frontier in the molecular biology of cancer with contributions from a noteworthy roster of leading scientists and clinicians, featuring an updated version of the classic "Hallmarks of Cancer" by Hanahan and Weinberg. See how molecular biology advances are impacting clinical practice with separate chapters on each of the 19 most common cancer types. Navigate the challenges and ethical dilemmas of cancer genetics with a thorough section chapters on genetic counseling and genetic testing. Now with the print edition, enjoy the bundled interactive eBook edition, offering tablet, smartphone, or online access to: Complete content with enhanced navigation, A powerful search that pulls results from content in the book, your notes, and even the web, Cross-linked pages, references, and more for easy navigation, A Highlighting tool for easier reference of key content throughout the text, Ability to take and share notes with friends and colleagues, Quick reference tabbing to save your favorite content for future use, See the inside front cover to find out how to access your eBook! Book jacket
Part I Principles of Oncology -- 1 The Cancer Genome / Yardena Samuels Samuels, Yardena, Alberto Bardelli Bardelli, Alberto, Jared J. Gartner Gartner, Jared J., Carlos López-Otin López-Otin, Carlos 1 -- 2 Hallmarks of Cancer: An Organizing Principle for Cancer Medicine / Douglas Hanahan Hanahan, Douglas, Robert A. Weinberg Weinberg, Robert A. 28 -- 3 Molecular Methods in Cancer / Larissa V. Furtado Furtado, Larissa V., Jay L. Hess Hess, Jay L., Bryan L. Belz Belz, Bryan L. 58 -- 4 Oncogenic Viruses / Christopher B. Buck Buck, Christopher B., Lee Ratner Ratner, Lee 78 -- 5 Inflammation / Sahdeo Prasad Prasad, Sahdeo, Bharat B. Aggarwal Aggarwal, Bharat B. 97 -- 6 Kinase Inhibitors as Anticancer Drugs / Charles L. Sawyers Sawyers, Charles L. 106 -- 7 Antiangiogenesis Agents / Cindy H. Chau Chau, Cindy H., William Douglas Figg, Sr. Figg, William Douglas, Sr. 122 -- Part II Molecular Biology of Individual Cancers -- 8 Molecular Biology of Head and Neck Cancers / Thomas E. Carey Carey, Thomas E., Mark E. P. Prince Prince, Mark E. P. 139 -- 9 Molecular Biology of Lung Cancer / Leora Horn Horn, Leora, Luiz Henrique de Lima Arattjo Arattjo, Luiz Henrique de Lima, Patrick Nana-Sinkam Nana-Sinkam, Patrick, Gregory A. Otterson Otterson, Gregory A., Terence M. Williams Williams, Terence M., David P. Carbone Carbone, David P. 147 -- 10 Molecular Biology of the Esophagus and Stomach / Anil K. Rustgi Rustgi, Anil K. 169 -- 11 Molecular Biology of Pancreas Cancer / Scott E. Kern Kern, Scott E., Ralph H. Hruban Hruban, Ralph H. 176 -- 12 Molecular Biology of Liver Cancer / Jens U. Marquardt Marquardt, Jens U., Snorri S. Thorgeirsson Thorgeirsson, Snorri S. 186 -- 13 Molecular Biology of Colorectal Cancer / Ramesh A. Shivdasani Shivdasani, Ramesh A. 194 -- 14 Molecular Biology of Kidney Cancer / W. Marston Linehan Linehan, W. Marston, Laura S. Schmidt Schmidt, Laura S. 211 -- 15 Molecular Biology of Bladder Cancer / Margaret A. Knowles Knowles, Margaret A., Carolyn D. Hurst Hurst, Carolyn D. 222 -- 16 Molecular Biology of Prostate Cancer / Felix Y. Feng Feng, Felix Y., Arul M. Chinnaiyan Chinnaiyan, Arul M., Edwin M. Posadas Posadas, Edwin M. 240 -- 17 Molecular Biology of Gynecologic Cancers / Tanja Pejovic Pejovic, Tanja, Michael J. Birrer Birrer, Michael J., Matthew L. Anderson Anderson, Matthew L., Kunie Odunsi Odunsi, Kunie 252 -- 18 Molecular Biology of Breast Cancer / Shaveta Vinayak Vinayak, Shaveta, Hannah L. Gilmore Gilmore, Hannah L., Lyndsay N. Harris Harris, Lyndsay N. 263 -- 19 Molecular Biology of Endocrine Tumors / Samuel A. Wells, Jr. Wells, Samuel A., Jr. 277 -- 20 Molecular Biology of Sarcomas / Samuel Singer Singer, Samuel, Torsten O. Nielsen Nielsen, Torsten O., Cristina R. Antonescu Antonescu, Cristina R. 288 -- 21 Molecular Biology of Cutaneous Melanoma / Michael A. Davies Davies, Michael A., Levi A. Garraway Garraway, Levi A. 308 -- 22 Molecular Biology of Central Nervous System Tumors / Victoria Clark Clark, Victoria, Jennifer Moliterno Günel Günel, Jennifer Moliterno, Mural Günel Günel, Mural 321 -- 23 Molecular Biology of Childhood Cancers / Lee J. Helman Helman, Lee J., David Malkin Malkin, David 332 -- 24 Molecular Biology of Lymphomas / Laura Pasqualucci Pasqualucci, Laura, Riccardo Dalla-Favera Dalla-Favera, Riccardo 346 -- 25 Molecular Biology of Acute Leukemias / Glen D. Raffel Raffel, Glen D., Jan Cerny Cerny, Jan 372 -- 26 Molecular Biology of Chronic Leukemias / James S. Blachly Blachly, James S., Christopher A. Eide Eide, Christopher A., John C. Byrd Byrd, John C., Anupriya Agarwal Agarwal, Anupriya 392 -- Part III Genetic Counseling -- 27 Genetic Counseling / Ellen T. Matloff Matloff, Ellen T., Danielle C. Bonadies Bonadies, Danielle C. 405 -- 28 Genetic Testing in Breast Cancer / Kristen M. Shannon Shannon, Kristen M. Anu Chittenden Chittenden, Anu 416 -- 29 Genetic Testing in Ovarian Cancer / Scott M. Weissman Weissman, Scott M., Shelly M. Weiss Weiss, Shelly M., Anna C. Newlin Newlin, Anna C. 429 -- 30 Genetic Testing in Colon Cancer (Polyposis Syndromes) / Kory W. Jasperson Jasperson, Kory W. 438 -- 31 Genetic Testing in Colon Cancer (Nonpolyposis Syndromes) / Leigha Senter-Jamleson Senter-Jamleson, Leigha 446 -- 32 Genetic Testing in Uterine Cancer / Molly S. Daniels Daniels, Molly S. 451 -- 33 Genetic Testing in Urinary Tract Cancers / Gayun Chan-Smutko Chan-Smutko, Gayun 456 -- 34 Genetic Testing in Pancreatic Cancer / Jennifer E. Axilbund Axilbund, Jennifer E., Elizabeth A. Wiley Wiley, Elizabeth A. 464 -- 35 Genetic Testing in Stomach Cancer / Nicki Chan Chan, Nicki, Jamas M. Ford Ford, Jamas M. 470 -- 36 Genetic Testing in the Endocrine System / Robert Pilarski Pilarski, Robert, Rebecca Nagy Nagy, Rebecca 481 -- 37 Genetic Testing in Skin Cancer / Michele Gabree Gabree, Michele, Meredith L. Seidel Seidel, Meredith L. 490
Abridgement of: Devita, Hellman, and Rosenberg's cancer. 10th edition. [2015]
Includes bibliographical references and index
1 13
Keywords: Cancer -- Genetic aspects; Neoplasms -- genetics; Neoplasms -- physiopathology; Cancer -- Molecular aspects